PENGARUH KEADILAN ORGANISASIONAL, KEPEMIMPINAN TRANSFORMASIONAL, DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL PADA KARYAWAN AYODYA RESORT - Darsana, I Wayan Agus; Putra, Made Surya (E-Jurnal Manajemen, 2017)
The purpose of this research was to determine the effect of organizational justice, transformational leadership and job satisfaction on organizational commitment on employee Ayodya Resort Bali. Samples taken as many as 183 people with proportional random sampling method. Data collection is done by distributing questionnaires using 5-point likert scale to measure 21 question items. Analysis technique used is multiple linear regression analysis using SPSS 13.00 for windows. The analysis showed that organizational justice positive and significant effect on organizational commitment. Transformational leadership is positive and significant effect on organizational commitment. Job satisfaction positive and significant effect on organizational commitment. The hotel should always pay attention to organizational justice, transformational leadership and job satisfaction of employees so that employees will have a high sense of commitment towards the organization.
Keywords: organizational justice, transformational leadership, job satisfaction, organizational commitment